TANGGUNG JAWAB TERHADAP PENCEMARAN LIMBAH PERTAMBANGAN BATU BARA DALAM PERSPEKTIF PERDATA DAN PIDANA - Arreza Saka Pahlawan Pahlawan (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRAK   This research is an Empirical Juridical research. data retrieval using interview results, better management of environmental management, it is proposed that the management of the company for its performance against environmental management law is supervised by the role of the two elements of stakeholders, namely Government and society on environmental management. in accordance with the provisions written in Law No.32 of 2009 on Environmental Protection and Management and Government Regulation No. 101 of 2014 on Hazardous and Toxic Waste Management and RKL and RPL documents, but the observation results appear that there are still management activities that not well implemented, ie monitoring of animals and lakes whose water is below the quality standard. Keywords: Pollution of Coal Waste, Government Regulation Number 101 Year 2014 About Waste Management of Hazardous and Toxic Substances